ANALISIS KINERJA KEUANGAN PERUSAHAAN DAERAH(STUDI KASUS PADA PERUSAHAAN DAERAH “RENGGANIS” KABUPATEN PROBOLINGGO JAWA TIMUR TAHUN 2018–2020) - Millah, Hayatul (universitas Islam Zainul Hasan Genggong, 2024)
This study aims to analyze the financial performance of the Regional Company “Rengganis” in Probolinggo Regency during the period 2018–2020. The method used is descriptive quantitative analysis with financial ratio techniques, including liquidity, solvency, activity, and profitability ratios. The results show an overall downward trend in financial performance, both in terms of liquidity and profitability, while the solvency ratio has increased. Factors contributing to this decline include rising operational costs, decreasing sales volume, and dependence on debt. This research is expected to serve as an evaluation material for management in making improvements to enhance the company's financial performance.